Effectiveness of quizizz in interactive teaching and learning Malay grammar - Munuyandi, Thulasirani; Husain, Salina; Abdul Jabar, Mohd Azidan; Jusoh, Zuraini (UiTM Press, 2021)
For teaching and learning Malay language grammar, there are many types of online assessment tools and applications have been developed in Malaysia. One such application is Quizizz, a game-based online quiz that facilitates teaching and learning. The purpose of this research is to measure the effectiveness of Quizizz application to teach and learn Malay grammar. We have used descriptive questionnaire research design, and chosen 130 students from Tamil schools by following the simple random sampling strategy. We have explored the effectiveness of Quizizz application as a formative quizzing tool for teaching and learning Malay grammar in year-four Tamil school students from 15 Tamil schools in Manjung district. The results showed that it was imperative to use Quizizz as a formative assessment tool to learn and teach Malay grammar to Tamil students. Students also responded positively to the use of Quizizz in the classroom through survey questionnaire results. At the end, we conclude that it is important for teachers to consider using fun and entertainment technology quizzing tools to teach Malay grammar.